THE INTERACTION OF SOCIAL STRATIFICATION AND KARONESE REGISTER IN GIVING PEDAH PEDAH PERJABUN - Elkana Putra Tarigan; Amrin . Saragih; Siti Aisyah Ginting (Universitas Negeri Medan, 2021)
Indonesia was well known for the variety of tribes, traditional languages, society and culture. It triggered to conduct this research that concerned to social stratification and Karonese register in giving pedah pedah perjabun. The problem of this research was how far the Karonese register change in this modern era or whether there were any differences among society group in Karonese traditional wedding ceremony. Based on this problem, this research aimed to 1) investigate the types of social stratification in traditional wedding ceremony of Karonese, 2) describe the reflections of social stratification toward the Karonese register, and 3) explain Karonese register in traditional wedding ceremony. This research was conducted by using descriptive qualitative design. The data were taken from Karonese register in traditional wedding ceremony and the source of data was Karonese native speaker who involved in traditional wedding ceremony. This research showed that 1) the interaction of Karonese society in traditional wedding ceremony stratifies Karonese people into four divisions. They are kalimbubu and anak beru that categorized as closed social stratification and sembuyak and teman meriah that categorized as opened social stratification, 2) social stratification were reflected through the differences and similarity form of register .Kallimbubu and anakberu used formal register as the most dominant regiser while sembuyak and anak beru used consultative register as the most dominant, and 3) the cause of Karonese register in traditional wedding ceremony was caused by register with reference to field that covered factor of arena and register with reference to tenor that cover formality and status. Keywords: Karonese Register, Pedah Pedah Perjabun; Social Stratification